Confronting complexity and unmet need: A qualitative study to inform palliative care service design for adults with multiple long-term conditions - Charlotte Stenson; Felicity Dewhurst; Philip Mordue; Katie Brittain; Mark Adley; Barbara Hanratty (Palliative Medicine, 2026)
Background: Most people live with and die from multiple long-term conditions. In the last year of life, many receive burdensome care of limited benefit, while access to palliative care remains inconsistent. Improving care for this population would help address inequity because disadvantaged groups are disproportionately affected. Aim: To examine professionals’ perspectives on palliative care needs and end-of-life challenges for people with multiple long-term conditions and their families, and to identify implications for service design and organisation. Design: Semi-structured interviews were analysed using cross-case comparison within reflexive thematic analysis. Setting/participants: Twenty-seven multidisciplinary professionals and decision-makers from health and social care in England were purposively sampled to include strategic and operational perspectives across specialities. Results: Three themes explored cumulative complexity, crisis-driven care and lack of ownership. Interacting conditions created complexity was unaddressed by disease-focused services, contributing to fragmented care and coordination burden. Care was reactive, with emergency responses and unplanned transitions associated with limited anticipatory planning. Responsibility for coordinating support was often unclear across service boundaries. Contributory factors included resource pressures, limited community workforce capacity and poor communication between services. Suggested service features included proactive review prompted by indicators of rising risk or deterioration, holistic multidisciplinary assessment with a relational, individualised approach to advance care planning, shared records and key worker roles. Conclusions: Current service organisation does not consistently meet palliative care needs in advanced multiple long-term conditions. Earlier risk recognition, clearer coordination responsibility and integrated multidisciplinary community provision are key priorities for improving care quality, sustainability and equity.